2015
DOI: 10.1002/int.21753
|View full text |Cite
|
Sign up to set email alerts
|

Folksonomy-Based Recommender Systems: A State-of-the-Art Review

Abstract: Collaborative tagging systems, also known as folksonomies, have grown in popularity over the Web on account of their simplicity to organize several types of content (e.g., Web pages, pictures, and video) using open-ended tags. The rapid adoption of these systems has led to an increasing amount of users providing information about themselves and, at the same time, a growing and rich corpus of social knowledge that can be exploited by recommendation technologies. In this context, tripartite relationships between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 104 publications
(143 reference statements)
0
16
0
3
Order By: Relevance
“…There are two methods to implement the KG representation learning: (1) tensor decomposition-based methods and (2) translation-based methods. The former includes NTN [15][16][17][18][19] and RESCAL [19][20][21][22]. The latter includes TransE [23][24][25], TransH [26][27][28][29], and TransR/CtransR [30][31][32].…”
Section: Knowledge Graph Representationmentioning
confidence: 99%
“…There are two methods to implement the KG representation learning: (1) tensor decomposition-based methods and (2) translation-based methods. The former includes NTN [15][16][17][18][19] and RESCAL [19][20][21][22]. The latter includes TransE [23][24][25], TransH [26][27][28][29], and TransR/CtransR [30][31][32].…”
Section: Knowledge Graph Representationmentioning
confidence: 99%
“…Along with the basic FolkRank, numerous researches are conducted on improving FolkRank [8,22,39,55]. Detailed information of the studies on collaborative tagging systems, also known as folksonomie can be found in a review paper [9]. Another survey paper compared the performance of different approaches of tagging systems focusing on adding semantics in folksonomies [18].…”
Section: Tag Recommendationmentioning
confidence: 99%
“…The collaborative filtering technology is generally divided into the method based on neighborhood and the method based on model [1]. The collaborative tagging is also called folksonomy [3], with which users can tag favorite resources freely for subsequent management and searching. Users describe resources with tags, so tags are the ties between users and resources.…”
Section: Related Workmentioning
confidence: 99%